2021
DOI: 10.1093/bib/bbab310
|View full text |Cite
|
Sign up to set email alerts
|

NeuroPpred-Fuse: an interpretable stacking model for prediction of neuropeptides by fusing sequence information and feature selection methods

Abstract: Neuropeptides acting as signaling molecules in the nervous system of various animals play crucial roles in a wide range of physiological functions and hormone regulation behaviors. Neuropeptides offer many opportunities for the discovery of new drugs and targets for the treatment of neurological diseases. In recent years, there have been several data-driven computational predictors of various types of bioactive peptides, but the relevant work about neuropeptides is little at present. In this work, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…AAC has been used as features for building many different models, ,,, which consists of the relative abundances of the 20 types of natural amino acids in a specified peptide segment. Given a kind of residue, R i represents the occurrent frequency of the residue; its relative abundance can be calculated as follows f i = R i N , goodbreak0em2em⁣ ( i = 1 , 2 , 3 , ... , 20 ) where N refers to the length of a specified peptide; thus, we can get the AAC feature vector of the peptide segment as F normalA normalA normalC = ( f 1 , f 2 , f 3 , ... , f 20 ) …”
Section: Materials and Methodsmentioning
confidence: 99%
“…AAC has been used as features for building many different models, ,,, which consists of the relative abundances of the 20 types of natural amino acids in a specified peptide segment. Given a kind of residue, R i represents the occurrent frequency of the residue; its relative abundance can be calculated as follows f i = R i N , goodbreak0em2em⁣ ( i = 1 , 2 , 3 , ... , 20 ) where N refers to the length of a specified peptide; thus, we can get the AAC feature vector of the peptide segment as F normalA normalA normalC = ( f 1 , f 2 , f 3 , ... , f 20 ) …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Many previous studies have shown that the ensemble model can achieve better predictive performance than single models in the ensemble, and reduce the generalization error of the prediction ( Charoenkwan et al., 2021 ; Mishra et al., 2019 ; Basith et al., 2022 ; Liang et al., 2021 ; Jiang et al., 2021 ; Guo et al., 2021 ). The existing ensemble learning strategies include boosting, bagging, and stacking ( Verma and Mehta, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Second, three-quarters of existing methods only applied a single algorithm. However, lots of studies have proven that the ensemble learning model usually outperforms the single-algorithm-based model ( Guo et al., 2021 ; Jiang et al., 2021 ; Basith et al., 2022 ; Liang et al., 2021 ; Mishra et al., 2019 ). Thus, the utilization of an ensemble learning strategy might improve the performance of AIP identification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we compared the proposed method with previously published methods such as PredT4SE-Stack and NeuroPpred-Fuse [55,56]. Therefore, our approach was only compared them from the structural aspect.…”
Section: Principle Of Machine Learning Algorithm and Fusion Modelmentioning
confidence: 99%